FUEL SUPPLY IN ACCUMULATOR DIESEL SYSTEMS WITH ELECTRONIC CONTROL AT STARTING REGIME - G. M. Kuharenok; A. N. Marchuk (Наука и техника)
The paper contains review and analysis of fuel supply process in accumulator diesel systems with electronic control at starting regime. The necessity has been shown to  develop and use programs of mathematic simulation pertaining to fuel supply processes with the purpose to decrease number of bench tests and time period required for a fuel system adaptation. The paper cites results of practical investigations on starting engines  equipped with the mentioned-above systems.